Correlation between lumbar skeletal muscle size and urinary incontinence after radical prostatectomy. Issue 3 (6th May 2020) - Mitsui, Yosuke; Sadahira, Takuya; Watanabe, Toyohiko; Araki, Motoo; Maruyama, Yuki; Sato, Ryota; Rodrigo, Acosta Gonzalez Herik; Wada, Koichiro; Watanabe, Masami; Chancellor, Michael B.; Nasu, Yasutomo
Abstract: Objectives: Urinary incontinence is a major concern after radical prostatectomy because it can decrease quality of life. The aim of the present study was to explore the effect of preoperative skeletal muscle on urinary quality of life after robot‐assisted radical prostatectomy. Methods: A total of 762 patients underwent robot‐assisted radical prostatectomy. Longitudinal health‐related quality of life was evaluated using the Expanded Prostate Cancer Index Composite instrument. The skeletal muscle area at the level of the third lumbar vertebra was assessed preoperatively by computed tomography and was standardized to height to obtain the skeletal muscle index. Reduced skeletal muscle size (RSMS) was defined as a skeletal muscle index ≤ 53 or ≤ 43 cm 2 /m 2 in patients with a body mass index (BMI) ≥25 or < 25, respectively. Results: A total of 301 patients were included in this study, of whom 91 were classified as having RSMS (30.2%). Non‐RSMS patients exhibited better urinary function at 12 months ( P = .012) and better urinary continence recovery at 2 weeks and 12 months ( P = .033 and P = .014, respectively) after prostatectomy compared with RSMS patients. Univariate and multivariate analyses identified preoperative RSMS as a significant and independent predictor of urinary incontinence (odds ratio = 1.77, P = .028). Conclusions: Patients with RSMS had a lower urinary quality of life compared with non‐RSMS patients after robot‐assisted radical prostatectomy, and RSMS, independent of age or BMI, was predictive of postoperative urinary incontinence.